2015
DOI: 10.1039/c4ta06024e
|View full text |Cite
|
Sign up to set email alerts
|

Cu2O nanorods modified by reduced graphene oxide for NH3 sensing at room temperature

Abstract: In this work, Cu 2 O nanorods modified by reduced graphene oxide (rGO) were produced via a two-step synthesis method. CuO rods were firstly prepared in graphene oxide (GO) solution using cetyltrimethyl ammonium bromide (CTAB) as a soft template by the microwave-assisted hydrothermal method, accompanied with the reduction of GO. The complexes were subsequently annealed and Cu 2 O nanorods/rGO composites were obtained. The as-prepared composites were evaluated using various characterization methods, and were uti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(55 citation statements)
references
References 45 publications
2
53
0
Order By: Relevance
“…Exposure of around 500 ppm ammonia can cause severe illness. In last few years ammonia sensing444546474849 has gained immense importance due to its toxic effects on human health and climate change. Most of them are electrical sensors with detection range starting from 1 to 1000 ppm.…”
Section: Ammonia Sensingmentioning
confidence: 99%
“…Exposure of around 500 ppm ammonia can cause severe illness. In last few years ammonia sensing444546474849 has gained immense importance due to its toxic effects on human health and climate change. Most of them are electrical sensors with detection range starting from 1 to 1000 ppm.…”
Section: Ammonia Sensingmentioning
confidence: 99%
“…There are many GR loaded with 6 metal oxide composites that are used in to gas sensors [30], supercapacitors [31] and lithium ion batteries [32]. However, the aggregation of reduced graphene oxide is hard to avoid and dramatically decreases the surface area, leading to a poor catalytic performance [33].…”
Section: Introductionmentioning
confidence: 99%
“…In this scenario, nanomaterials based chemiresistive sensors have gained much attention in recent years owing to their simple operating principle and device fabrication. Several recent studies have demonstrated the feasibility of high performance NH 3 sensors using various nanomaterials including metal oxide nanostructures, carbon nanotubes (CNTs), conducting polymers, graphene, etc. Among these materials, CNTs have attracted considerable interest as sensing materials, owing to their unique physical and chemical properties, large surface‐to‐volume ratio and room temperature operation .…”
Section: Introductionmentioning
confidence: 99%